Performing to a world class standard under pressure - Can we learn lessons from the Olympians? - Colbert, S. D.; Scott, J.; Dale, T.; Brennan, P. A. (British Journal of Oral and Maxillofacial Surgery, 2012)
With the 2012 Olympics being held in London, we explored pre-requisites for success in sport, and the comparative efficacy of employing these when performing under intense pressure in the clinical setting. We asked members of the Great Britain Olympic rowing team and OMFS surgeons to complete a validated questionnaire on how they performed under pressure. 89 questionnaires were completed by 43 surgeons and 46 rowers (81% response). We compared the results in terms of mental toughness and technical skill. The importance of training to be a winner was evident in athletes. While emphasising the multidimensional nature of talent, we recognise the essential role of psychology in the ability of individuals to fulfil their sporting potential. We discuss the possible implications for surgeons.